The religious significance of the medieval body and Flannery O'Connor's fiction. - Novak, Kenneth Paul. (University of Ottawa (Canada), 2002)
Flannery O'Connor based what she called her "anagogic vision" on the medieval way of seeing the world that allowed the reader of a text to discern "different levels of reality in one image or one situation." In my thesis I focus on the ways in which O'Connor revives this literary strategy and adapts it to address the modern cultural context. Accordingly, I examine in particular how her fiction engages Descartes' worship of consciousness and Nietzsche's supposition that "God is dead" by anagogically endowing her characters' bodies with two layers of signification. The first signified body is the spiritually-dead body, which belongs to the character who believes he is a god unto himself by virtue of his intellect. Since the character accepts his mind as his essence of being, his body appears in O'Connor's stories as the image of a soulless identity, a corpse. When the character recognizes the rightful place of the soul, the whole person emerges from the second signified body.
Keywords: Literature, Modern.